Interplay between hydrophilic and hydrophobic interactions for deciding the molecular orientation in Langmuir-Blodgett film deposition - Mukhopadhyay, M; Sanyal, M; Datta, A; Webster, J; Penfold, J (2005)
The results of X-ray and neutron scattering, and Fourier transform infrared (FTIR) studies presented here to understand the effect of hydrophilicity or hydrophobicity of substrate in determining molecular orientation of three-tailed amphiphilic salt ferric stearate in Langmuir-Blodgett films. Molecules in the first monolayer deposited on hydrophilic substrate are in asymmetric configuration but molecules in subsequent monolayers are in symmetric configuration as hydrophobic interaction becomes dominant. This symmetric molecular configuration is retained right from first monolayer deposition on hydrophobic substrate. FTIR studies reaffirm the asymmetric molecular configurations in the first layer and symmetric structure from the subsequent transferred layers on hydrophilic substrates. © 2005 Elsevier B.V. All rights reserved.